Study in ovo immunisation with flagellin and whole cell protein antigens of Campylobacter jejuni in chickens - Noor, Susan Maphilindawati; Husband, Alan J (Indonesian Journal of Animal and Veterinary Sciences, 2000)
In ovo immunisation of chickens with flagellin and whole cell protein antigens of Campylobacter jejuni was examined to determine Campylobacter infection. Four groups of embryonated chicken eggs (10 eggs per group) were immunised in ovo at day 17 of incubation and booster was given at 7 days post-hatch. Group I was immunised in ovo and oral booster with whole cell protein of C. jejuni, group II was immunised in ovo and oral booster with C. jejuni flagellin protein, group III was immunised in ovo and intraperitoneal booster with whole cell, and group IV was treated as control. The humoral immune responses were determined by enzyme-linked immunosorbent assay (ELISA) and the mucosal immune responses were examined by a direct fluorescent histology antibody technique. Immunised chickens of Group I, II, and III shown to have higher antibody titers thanÂ  those of control chickens (group IV). The titres of anti-campylobacter antibodies of all isotypes in serum, bile, and intestinal scrapping after challenge were not significantly different in all groups. In addition, when immunised chickens were orally challenged with a homologous strain of viable C. jejuni organism, the chickens remained infected throughout the experiment based on cloacal swabs and caecal contents. These findings indicated that although in ovo immunisation resulted in increasing of the mucosal and humoral immune responses in chickens, it is not strong enough to protect the Campylobacter colonisation in the intestinal tract. Â  Key words : In ovo immunisation, Campylobacter jejuni, whole cell, flagellar, chickens